2011
DOI: 10.1093/cercor/bhr023
|View full text |Cite
|
Sign up to set email alerts
|

Sound to Language: Different Cortical Processing for First and Second Languages in Elementary School Children as Revealed by a Large-Scale Study Using fNIRS

Abstract: A large-scale study of 484 elementary school children (6–10 years) performing word repetition tasks in their native language (L1-Japanese) and a second language (L2-English) was conducted using functional near-infrared spectroscopy. Three factors presumably associated with cortical activation, language (L1/L2), word frequency (high/low), and hemisphere (left/right), were investigated. L1 words elicited significantly greater brain activation than L2 words, regardless of semantic knowledge, particularly in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 144 publications
6
47
0
Order By: Relevance
“…In late bilinguals who have asymmetric proficiency between languages, the right PFC may play a part in switching between languages with selection of phonological representations from the non-dominant language lexicon. Additionally, a recent study reported that acquiring unfamiliar words, an important ability for second language learning, elicited more right prefrontal activation than left in children (Sugiura et al, 2011). The present study has shown for the first time that the engagement of the right PFC in language switching processes may be proficiency dependent.…”
Section: Tablesupporting
confidence: 61%
“…In late bilinguals who have asymmetric proficiency between languages, the right PFC may play a part in switching between languages with selection of phonological representations from the non-dominant language lexicon. Additionally, a recent study reported that acquiring unfamiliar words, an important ability for second language learning, elicited more right prefrontal activation than left in children (Sugiura et al, 2011). The present study has shown for the first time that the engagement of the right PFC in language switching processes may be proficiency dependent.…”
Section: Tablesupporting
confidence: 61%
“…First, the advantage of HOE over AOFE is somewhat unexpected because the effects of AOFE have Language acquisition and brain development been reported repeatedly in previous behavioral studies (Yamada, Takatsuka, Kotake andKurusu 1980: Johnson andNewport 1989;DeKeyser 2000), supporting the advantages of early starters in phonological skills and syntax learning. The discrepancy of the results in the previous behavioral studies and those in Ojima, Matsuba-Kurita et al (2011) might be due to different phases or stages of learning. Previous behavioral studies on ongoing L2/FL learning have reported that late starters are faster learners than early starters even in syntax, suggesting the advantage of late starters in the speed of learning (Munoz 2006;Snow and HoefnagelHohle 1978).…”
Section: Erp Studies Of Semantic Comprehension Of Spoken Words In Japmentioning
confidence: 57%
“…environment, and learning strategy. Ojima, Matsuba-Kurita et al (2011) focused on the age of first exposure (AOFE) and total hours of exposure (HOE). Based on a total of 815 ERP datasets obtained longitudinally from 350 children who participated in the cohort study, children's English proficiency scores and N400 amplitude were analyzed in multiple regression analyses.…”
Section: Erp Studies Of Semantic Comprehension Of Spoken Words In Japmentioning
confidence: 99%
See 2 more Smart Citations